2010
DOI: 10.1038/hr.2010.241
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal blood pressure variation and related behavioral factors

Abstract: Blood pressure (BP) varies according to many internal and external factors, and behavioral factors have an important role in diurnal BP variation. BP rises sharply on waking in the morning and falls during sleep at night, although it varies throughout the day and night. These changes in BP are closely related to mental and physical activities, and the sympathetic nervous system mainly contributes to the diurnal variation in BP. Other behavioral factors, such as food consumption and obesity, dietary intake of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 71 publications
0
69
1
1
Order By: Relevance
“…Although increased HBP variability might reflect the disease state, physiological or behavioral factors may also influence HBP variability. These factors, including waking and sleep cycles, mental and physical stress, temperature and alcohol intake, can affect diurnal BP variability, and may also be associated with HBP variability [22,23,31,32]. In addition, the quality of HBP measurements is not uniform, and artificial factors related to BP measurements, such as a time of resting before measurement, posture, or cuff placement, might be associated with variability.…”
Section: Discussionmentioning
confidence: 94%
“…Although increased HBP variability might reflect the disease state, physiological or behavioral factors may also influence HBP variability. These factors, including waking and sleep cycles, mental and physical stress, temperature and alcohol intake, can affect diurnal BP variability, and may also be associated with HBP variability [22,23,31,32]. In addition, the quality of HBP measurements is not uniform, and artificial factors related to BP measurements, such as a time of resting before measurement, posture, or cuff placement, might be associated with variability.…”
Section: Discussionmentioning
confidence: 94%
“…Blood pressure differences could be explained by diurnal rhythm of systemic blood pressure, dipping at night (behavioral sleep period) and surging at the time of waking in the morning (45). In KoGES, blood pressure is typically measured between 8 AM and noon.…”
Section: Discussionmentioning
confidence: 99%
“…8,[24][25][26][27][28][29] In addition, various physiological or behavioral factors, including waking and sleep cycles, mental and physical stress, temperature, and alcohol intake can affect both HBPV and VVV. [30][31][32][33][34] Previous studies have shown the factors affecting HBPV, including older age, female gender, high HBP and alcohol intake. 25,[30][31][32] The factors affecting VVV were almost similar to those affecting HBPV in several studies, including older age, female gender, high mean systolic clinic BP and history of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%